Protective Effects of N-Acetylcysteine in Alleviating Cocaine-Mediated Microglial Activation and Neuroinflammation - Uma Maheswari Deshetty; Abiola Oladapo; Yazhini Mohankumar; Elias Horanieh; Shilpa Buch; Palsamy Periyasamy (Biology)
Cocaine misuse induces microglial activation and neuroinflammation, contributing to neurodegeneration and behavioral impairments. Prior studies have shown that cocaine induces mitochondrial dysfunction, dysregulated mitophagy, and lysosomal impairment in microglia. Here, we investigated the therapeutic potential of N-acetylcysteine (NAC) in mitigating cocaine-induced microglial activation and neuroinflammation. Mouse primary microglial cells (MPMs) were pretreated with NAC (5 mM) for 1 h prior to cocaine exposure (10 µM, 24 h) and analyzed for markers of microglial activation, mitophagy, and lysosomal integrity using Western blot, Seahorse assays, lysosomal pH, and membrane potential measurements. In vivo, C57BL/6N mice received NAC (200 mg/kg, i.p.) 1 h before daily cocaine injections (20 mg/kg, i.p.) for 7 days. Behavioral assays (open field, novel object recognition) and brain biomarker analyses (frontal cortex, hippocampus) were performed. Cocaine exposure elevated CD11b, mitophagy markers (PINK1, PARK, and DLP1), and autophagy proteins (Beclin1, and p62), while impairing mitochondrial and lysosomal functions. NAC pretreatment restored mitochondrial and lysosomal function, reduced reactive oxygen species, and normalized protein expression. In vivo, NAC also alleviated cocaine-induced microglial activation and behavioral deficits. These findings highlight NAC as a promising therapeutic agent to counteract cocaine-mediated neuroinflammation and neurotoxicity.